Evrimsel Topolojik Optimizasyon Yöntemiyle Delikli Kirişlerin Bükülmesinin Boyut Analizi - Çelik, Ender; Savaş, Vedat (Altınbaş University, 2022)
The aim of this study is to determine the optimal shape and clearance of the web openings in order to both increase the carrying capacity and decrease the weight of classic perforated beams by using evolutionary topological optimization technique. The effects of the optimal shape and web openings has been obtained by the application of the evolutionary topological optimization through finite elements method, and then the obtained optimal beam has been compared with widely used perforated beams in the market by using stress and displacement analysis. The designed beam was seemed to have more advantages then the widely used ones in industry with a less weight and higher carrying capacity. With the topology optimization, the usual classic perforated beams’ geometry has been changed and stiffness was improved.
Dimension Analysis of Bending Perforated Beams with the Evolutionary Topological Optimization Method
Keywords: Engineering; Mühendislik